Economic evaluation of acupuncture as an adjunctive treatment with usual care for mild-to-moderate knee osteoarthritis: A Markov model-based analysis - Eunhye Hyun; Byung-Cheul Shin; NamKwen Kim; Byungmook Lim (Integrative Medicine Research)
Background: Collaborative care (CC), in which acupuncture is combined with usual care (UC), improves clinical outcomes and increases costs in knee osteoarthritis (KOA). We evaluated the economic feasibility of CC for Korean female patients with mild-to-moderate KOA by using a cost-effectiveness approach. Methods: Two alternatives for KOA (1. UC as a comparator; and 2. CC as an intervention) were defined based on clinical guidelines, official Korean statistics, and expert validation. Each alternative was simulated in a Markov model every 6 months for 10 years. Estimates of costs, utilities, and transition probabilities were obtained from official statistics and previous studies. The effectiveness of CC was synthesized from randomized controlled trials. A base-case analysis of a limited societal perspective, univariate sensitivity analysis, and probability sensitivity analysis were performed. An annual discount rate of 4.5% and threshold of 20,000 United States dollar per Quality-adjusted life year (USD/QALY) were applied. Results: Every incremental cost-effectiveness ratio (ICER) of CC calculated from the analyses was sub-threshold. In the base-case analysis, with a limited societal perspective, the ICER was 11,085 USD/QALY. The ICERs from the univariate sensitivity analyses were -2,577–16,748 USD/QALY. The average ICER in the probability sensitivity analysis was 12,412 USD/QALY. When the threshold surpassed 8,000 USD/QALY, the cost-effectiveness of CC exceeded 50%. The probability was 70.27% when the threshold was 20,000 USD/QALY. Conclusions: CC for Korean female patients with mild-to-moderate KOA was generally cost-effective. Considering the limitations of the evidence, we propose a re-evaluation using further clinical studies in the future.